Recurrence Relations for Single and Product Moments of Ordinary Order Statistics from pth Order Inverse Exponential Distribution - Arora, Rajat; Sachdev, Rajesh (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper, we establish some recurrence relations satisfied by single and productinverse moments of ordinary order statistics from pth order inverse exponentialdistribution. These recurrence relations are generalized versions of recurrence relationsfound by Joshi (1978, 1982), Balakrishnan and Rao (1998), Balakrishnan and Malik(1986a, b), Balakrishnan and Joshi (1984) and Mohie El-Din et al. (1997) andNain(2010a, b).